Gradient Descent and Twice Differentiable Simpson-Type Inequalities via K-Riemann-Liouville Fractional Operators in Function Spaces (European Journal of Pure and Applied Mathematics, 2025)
This paper investigates novel properties of Hilbert spaces through tensor operations and establishes new bounds for Simpson-type inequalities using fractional integral operators. The results contribute to advancing the theoretical understanding of these mathematical structures and their applications in functional analysis and related fields.